Dual‐site right ventricular pacing in patients undergoing cardiac resynchronization therapy: Results of a multicenter propensity‐matched analysis. Issue 10 (15th September 2017) - Providencia, Rui; Barra, Sergio; Papageorgiou, Nikolaos; Ioannou, Adam; Rogers, Dominic; Wongwarawipat, Tanakal; Falconer, Debbie; Duehmke, Rudolf; Colicchia, Martina; Babu, Girish; Segal, Oliver R.; Sporton, Simon; et al.
Abstract: Background: Dual‐site right ventricular pacing (Dual RV) has been proposed as an alternative for patients with heart failure undergoing cardiac resynchronization therapy (CRT) with a failure to deliver a coronary sinus (CS) lead. Only short‐term hemodynamic and echocardiographic results of Dual RV are available. We aimed to assess the long‐term results of Dual RV and its impact on survival. Methods: Multicenter retrospective assessment of all CRT implants during a 12‐year period. Patients with failed CS lead implantation, treated with Dual RV, were followed and assessed for the primary endpoint of all‐cause mortality and/or heart transplant. A control group was obtained from contemporary patients using propensity matching for all available baseline variables. Results: Ninety‐three patients were implanted with Dual RV devices and compared with 93 matched controls. During a median of 1, 273 days (interquartile range 557–2, 218), intention‐to‐treat analysis showed that all‐cause mortality and/or heart transplant was higher in the Dual RV group (adjusted hazard ratio [HR] = 1.66, 95% confidence interval [CI] 1.12–2.47, P = 0.012). As‐treated analysis yielded similar results (HR = 1.97, 95% CI 1.31–2.96, P = 0.001). Cardiac device‐related infections occurred seven times more frequently in the Dual RV site group (HR = 7.60, 95% CI 1.51–38.33, P = 0.014). Among Dual RV nonresponders, four had their apical leads switched off, five required an epicardial LV lead insertion, a transseptal LV lead was implanted in two, and in nine patients, after reviewing the CS venogram, a new CS lead insertion was successfully attempted. Conclusion: Dual RV pacing is associated with worse clinical outcomes and higher complication rates than conventional CRT.